MOTIVATION OF RICE FARMERS IN USING PLANT GROWTH PROMOTING RHIZOBACTERIA AT SEKAYU DISTRICT, MUSI BANYUASIN REGENCY - Supriyadi, Didik; Tasrif, Arifin; Kisworo, Arif Nindyo (Jurnal Penyuluhan Pertanian, 2023)
One of the most common problems in agriculture today is the decline in soil fertility on agricultural land due to the excessive use of chemical fertilizers and pesticide residues and processing of land with agricultural machinery. This study was to determine the level of motivation for using PGPR in lowland rice cultivation, what factors influence the level of motivation, as well as developing a strategy for applying motivation using PGPR in lowland rice cultivation. This research was conducted from April to June in Sekayu District, Musi Banyuasin Regency. The method used is descriptive method and multiple linear regression. Respondents were taken as many as 97 people who were determined purposively (purposive sampling). The results show that the level of motivation is included in the high category. Factors that have a significant effect on farmer motivation are the age of the farmer, the role of extension workers, the availability of facilities and infrastructure, the availability of agricultural information. Based on the multiple linear regression analysis test, it was found that the most critical indicator of farmer motivation was the availability of facilities and infrastructure. From these results an agricultural extension strategy was providing counseling on making PGPR independently in farmer groups.